Application of Multi Objective land Allocation technique for land use Planning Approach Case study: Hamadan County - hassan mahmodzadeh; sodabeh panahi; mahdi herischian (تحقیقات کاربردی علوم جغرافیایی)
From the late  twentieth century, human kind has found out that if he wants to obtain cost efficiently and continuous utilization of lands, it is better to execute this in a planned framework named management plan. Such idea is became  as an introduction to monitor the land or utilization of lands. Monitoring lands means contribution of an optimized space for land utilization with realization of common upcoming and related to each other in the past, now and in the future.Therefore, the objective  of  this research is to select the suitable lands  with monitoring lands of view in the city of Hamedan using a Multi-Objective Land Allocation method.The aim of Multi-Objective Land Allocation  method use is to contribute  selection of proper lands with monitoring approach based on ideal levels concept which have been executed by 3 different ecologic, socio-economic and strategic aspects existing in the territory.The examined use include agricultural use (water system or dry farming), pasturing use and urban use which based on the highest weight of independent variables, the area has been allocated to mentioned use with land monitoring approach.In what follows, the land suitability map is obtained through MCE operation for each type of land use and the obtained land suitability areas were calculated using these maps for which the results are as follows: irrigated agriculture with 601.176 hectares, dryland farming with 961.193 hectares, urban suitability with 762.984, and rangeland management suitability with 960.552 hectares which is an important criterion for determining the area for implementing MOLA.In the next step, it was time for implementing MOLA module for resolving the contradictions among the  uses.The results of MOLA showed that in average for the three studied aspects, the maximum area was associated with dryland farming with 364.4 hectares which is equivalent to 32% of the studied uses and the maximum weight of 0.4 was associated with irrigated agriculture.These resulted were obtained based on five factors (i.e. the current area of each land use, the favorable area for each land use based on MCE method, the occupational dependencies of different individuals to each land uses, prioritizing the ecological, economic, and social aspects of each land use).Finally, the results showed that selecting the suitable lands with spatial planning point of view using a Multi-Objective Land Allocation method is carried out properly through economic, social, and ecological aspects.